The Law of Christ and the Law of Moses: Reflections on a Recent Trend in Interpretation - Wilson, Todd A. (Currents in biblical research, 2006)
The expression “law of Christ” (Gal. 6.2) continues to bedevil interpreters of Galatians, not least because it seems entirely out of place in a letter otherwise devoted to distancing Christ from the law (cf. 5.4). While the phrase has traditionally been understood to refer to that whichreplaces the law of Moses, there has been a significant shift of opinion in recent years. Now many interpreters want to read the expression as a direct reference to the law of Moses. This essay traces the emergence of this recent trend, situates it within its broader exegetical and theological milieu and considers some of the main exegetical arguments used to support the reading. The essay then concludes with a few reflections on the implications of this interpretive trend for Pauline exegesis.